Detection of Pork in Canned Meat Products by using DNA-based Methods - Alaa Tariq Abdulwahid (Indian Journal of Forensic Medicine & Toxicology, 2021)
Adulteration of meat products became a matter of great concerns of religious, economical, legal and hygienicaspects. Canned meat is one of the most favorable in a lot of countries, which makes it prone to adulteration.The objective of the current study was to identify pork in canned meat for the presence of adulteration incommercial market of Basrah city/Iraq. Thirty canned meat were collected from commercial market. Thepossibility of a species mixture was tested with polymerase chain reaction (PCR), targeting pork (290bp).Analysis of canned meat revealed negativity results of all samples to pork meat. In conclusion, samplesanalysed in the current study showed that there was no adulteration by mixing pork meat in canned meatproducts due to absent production of pork flesh for religion and hygienic aspects. Beef and mutton fleshmight be replaced in chicken, horse, and donkey flesh for economic reason.